Perancangan Aplikasi Go Grouph Math sebagai Sarana Penyelesaian Tugas Kelompok - Shinta Dwi Handayani; Aulia Paramita; Alusyanti Primawati (SAP (Susunan Artikel Pendidikan), 2021)
The purpose of this research is to design an android-based groupware called Go Group Math as part of the media or application to support group work in particular which can later be used for mathematics subjects. The method used in this research was Research and Development (RnD) using the ADDIE model, namely Analyze, Design, Development, Implementation, and Evaluation. Activities in research carried out in this research have only reached the stage of designing a screen display that will be used later in the application development stage using various database sources. The results of this study discovered that there was already a display screen design that will be used as a screen display on an Android smartphone. This research was expected to be useful for various groups in the world of education, especially teachers, lecturers, students, and students.